2009
DOI: 10.1111/j.1574-695x.2009.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

A TonB-dependent outer membrane protein as aBacteroides fragilisfibronectin-binding molecule

Abstract: The binding of Bacteroides fragilis to plasmatic fibronectin was investigated using strains isolated from healthy subjects and from patients with bacteremia. They were cultivated in a synthetic media in which variations in cysteine concentrations determined alterations in the oxidation-reduction potential (Eh). All the strains assayed were capable of adhering to plasmatic fibronectin when cultivated under oxidizing and reducing conditions. Bacteroides fragilis 1405 showed the greatest difference when the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…This conclusion is in agreement with the observation that fibronectin binds TonBdependent outer membrane receptors present in Bacteroides fragilis, P. multocida, and A. baumannii (39,48,52). However, the molecular factors and processes involved in these interactions are not clear at the moment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This conclusion is in agreement with the observation that fibronectin binds TonBdependent outer membrane receptors present in Bacteroides fragilis, P. multocida, and A. baumannii (39,48,52). However, the molecular factors and processes involved in these interactions are not clear at the moment.…”
Section: Discussionsupporting
confidence: 78%
“…However, the molecular factors and processes involved in these interactions are not clear at the moment. The conclusion that fibronectin binds TonB (39,52) is not in agreement with the known subcellular location and topology of TonB. This is a cytoplasmic membraneanchored protein that spans the periplasmic space, interacts with the N-terminal domain of TonB-dependent outer membrane receptors, and most likely is not exposed to the extracellular environment.…”
Section: Discussionmentioning
confidence: 49%
“…The function of TonB is apparently to transduce energy to the outer membrane receptors, perhaps by releasing otherwise tightly bound ligands into the periplasmic space [26], [27]. Apart from its capacity to transport molecules, in Pasteurella multocida and Bacteroides fragilis , TonB is able to recognize and bind to fibronectin [22], [28]. It also has been suggested that TonB may allow some species to adhere to and colonize different niches in the host [28].…”
Section: Discussionmentioning
confidence: 99%
“…Particle agglutination assay. Latex particles (0.83 mm diameter; Sigma) coated with plasma fibronectin (Sigma) were prepared according to Pauer et al (2009). All the B. fragilis strains were grown for 18 h at 37 uC in BHI broth, centrifuged (3000 g for 10 min) and washed once in 0.1 M PBS (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%